Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538930
|View full text |Cite
|
Sign up to set email alerts
|

No tests required

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Both traditional machine-learning methods and transfer-learning methods show reasonable performance in determining whether the student will pass the course. This result is in line with previous studies that have identified the possibility of assessing students' performance based on various process-and background-based metrics [1,19,22,32,34,38]. However, when comparing our study to the previously mentioned ones, the difference in context was significantly larger, and our study had rather generalized features.…”
Section: Determining Students' Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…Both traditional machine-learning methods and transfer-learning methods show reasonable performance in determining whether the student will pass the course. This result is in line with previous studies that have identified the possibility of assessing students' performance based on various process-and background-based metrics [1,19,22,32,34,38]. However, when comparing our study to the previously mentioned ones, the difference in context was significantly larger, and our study had rather generalized features.…”
Section: Determining Students' Performancesupporting
confidence: 91%
“…Error quotient and its relatives (see, e.g., References [2,5,38]) are approaches where the data used for the outcome prediction has required significant insight into the programming process and the internals of the used programming language. This is not necessary, however, as one can also use higher level information such as the number of actions or attempts that a student makes on assignments as a feature [1,6].…”
Section: Predicting Course Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these are based on analysis of student interaction with the programming language compiler, such as: investigating novice programming mistakes [1]; exploring compilation behavior [16]; analyzing response to compiler error messages [23]. Other studies focus on comparing and testing traditional predictors of performance and new datadriven predictors [27]. Several works have found that the mathematical ability and exposure to mathematics courses are important predictors of performance on introductory programming courses [25,28,30].…”
Section: Related Workmentioning
confidence: 99%
“…In 2017, Kirkpatrick et al introduced an alternative CS1 for students with prior programming knowledge [25]. Predicting & measuring success [6,46] and research on Programming process data [2] have also only appeared since the turn of the century. It is interesting to note that concerns about large enrollments appeared as early as 1974 [11], while Retention, dating back as far as 1984, has shown significant interest more recently [34].…”
Section: Teachingmentioning
confidence: 99%